CULTURE-SPECIFIC ITEMS AND TRANSLATION STRATEGIES IN TIM OBRIENS THE THINGS THEY CARRIED AND ITS INDONESIAN TRANSLATION - Seannovika, Maria; Darta, Deta Maria Sri (Sanata Dharma University, 2024)
As one of the most complicated concepts to translate, a number of translators and researchers have presented various strategies to transfer the meaning of culture-specific items (CSIs) from one language to another. Through eight translation strategies used by professional translators based on Baker, this paper aimed to find the most applicable strategy to find a way around culture-specific items. In addition, this paper also attempted to categorize CSIs found in Tim OBriens The Things They Carried according to Newmarks five taxonomies of foreign cultural words. The comparative model in translation studies and comparative research were applied as methods to obtain and analyze data from both the source text and target text. The results showed that out of five taxonomies, social culture has the highest percentage overall with 45%. Furthermore, translation by paraphrase using unrelated words also has the highest percentage among the eight translation strategies with 31%. Therefore, it can be concluded that translation by paraphrase using unrelated words is the most applicable strategy to translate CSIs found in The Things They Carried.